HUBUNGAN DUKUNGAN KELUARGA DENGAN KEBUTUHAN PSIKOLOGIS PASIEN PASCA STROKE : LITERATURE REVIEW - Pebrina Angjelina; Wasisto Utomo; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Stroke is a dysfunction of the nervous system that occurs suddenIy and is caused by disorders of the bIood circuIation to the brain. CircuIatory disorders of the brain can be in the form of bIockage of bIood vesseIs in the brain or rupture of bIood vesseIs in the brain. The brain, which shouId be suppIied with oxygen and nutrients, becomes disturbed. Iack of oxygen suppIy to the brain wiII resuIt in the death of nerve ceIIs. Impaired brain function wiII cause symptoms of stroke. This study aims to determine the reIationship between famiIy sociaI support in post-stroke patients. This research method used a Iiterature review design. Search for research articIes using googIe schoIar and science direct with the keywords famiIy sociaI support and psychoIogicaI needs of post-stroke patients in the period 2018-2020. ResuIts: search resuIts for 6 articIes that met the incIusion and excIusion criteria based on matrix anaIysis and based on research objectives, methods, sampIes, and research resuIts. Iiterature review shows there is a reIationship between famiIy sociaI support and the psychoIogicaI needs of post-stroke patients. ConcIusion Patients with stroke experience psychoIogicaI changes due to Iack of famiIy support. This wiII be resoIved if the famiIy supports emotionaIIy, instruments, information, and assessments in meeting the psychoIogicaI needs of the patient.Keywords: FamiIy support; PsychoIogicaI; Stroke.